An Explainable AHP with Sensitivity Analysis Approach for Strategic IT Project Prioritization in Higher Education - Hilyah Magdalena; Ade Septryanti (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study addresses the strategic challenges faced by private universities in Indonesia in selecting the most suitable IT project to support digital transformation, comparing a Next-Generation Learning Management System (LMS) and an Integrated University Mobile Super-App. Rather than developing a new method, this study enhances the conventional Analytical Hierarchy Process (AHP) by integrating sensitivity analysis and priority decomposition to improve decision explainability (Explainable MCDM). Expert assessments were collected from five academic stakeholders using pairwise comparisons based on Saaty's scale. Four criteria were assessed: Strategic Alignment, Benefits & Impact, Feasibility & Resources, and Risk Assessment. The results show a narrow preference for the LMS (50.7%) over the Super-App (49.3%), primarily driven by its superiority on the highest-weighted criterion, Strategic Alignment (35.6%), particularly the